2020
DOI: 10.1186/s12885-020-07495-9
|View full text |Cite
|
Sign up to set email alerts
|

The Axin2-snail axis promotes bone invasion by activating cancer-associated fibroblasts in oral squamous cell carcinoma

Abstract: Background In bone-invasive oral squamous cell carcinoma (OSCC), cancer-associated fibroblasts (CAFs) infiltrate into bony tissue ahead of OSCC cells. In the present study, we aimed to investigate the role of the Axin2-Snail axis in the biological behaviour of CAFs and bone invasion in OSCC. Methods The clinicopathological significance of Axin2 and Snail expression was investigated by immunohistochemistry in an OSCC cohort containing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Snail, a transcriptional repressor of E-cadherin, is overexpressed in a variety of cancers and promotes the proliferation, invasion, and tumorigenesis of cancer cells ( 46 , 47 ). Moreover, Axin2 and Snail expression were significantly associated with some of the classic poor prognostic indicators, such as lymph node metastasis, vascular invasion, and bone invasion in various types of cancers including OSCC ( 48 50 ). In our previous studies, we found that the Axin2–Snail axis is significantly related to malignant transformation of oral leukoplakia ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Snail, a transcriptional repressor of E-cadherin, is overexpressed in a variety of cancers and promotes the proliferation, invasion, and tumorigenesis of cancer cells ( 46 , 47 ). Moreover, Axin2 and Snail expression were significantly associated with some of the classic poor prognostic indicators, such as lymph node metastasis, vascular invasion, and bone invasion in various types of cancers including OSCC ( 48 50 ). In our previous studies, we found that the Axin2–Snail axis is significantly related to malignant transformation of oral leukoplakia ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bone invasion of OSCC is classified into three types: Erosive, infiltrative and mixed ( 31 , 32 ). A previous study reported that the interaction between cancer-associated fibroblasts and cancer cells promoted bone invasion and prognosis of OSCC ( 27 ). The present study demonstrated that bone invasion of the HSC-3 + G-SCs group was of the mixed type, whereas the bone invasion of the HSC-3 + P-SCs group was erosive.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthetization of mice was confirmed by assessing whether mice returned to a prone position when placed on their backs. Following intraperitoneal anesthesia, 200 µl mixed cells (HSC-3, 1×10 6 , 100 µl mixed with G-SCs, P-SCs or HDFs, 3×10 6 , 100 µl) were injected into subcutaneous tissue on the top of the head of 20 healthy female BALB-nu-nu mice (age, 4 weeks; mean weight, 15 g; Shimizu Laboratory Supplies Co., Ltd.), as previously described ( 27 ). All mice were kept in the animal center of Okayama University, Okayama, Japan (25°C; 50–60% humidity; 12/12-h light/dark cycle) and had free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“…All animal experiments were conducted according to the relevant guidelines and regulations, and were approved by the institutional committees at Okayama University (OKU-2017406). Following intraperitoneal anesthesia with ketamine hydrochloride (75 mg/kg body weight) and medetomidine hydrochloride (0.5 mg/kg body weight), 200 µ l mixed cells including HSC-3 (1×10 6 , 100 µ l) and stromal cells (VSCC-SCs, SCC-SCs and HDFs, 3×10 6 , 100 µ l) were injected into the central region of the top of the head (in the lamina propria) of 12 BALB/c nu-nu mice (4-week-old healthy females) obtained from SHIMIZU Laboratory Supplies Co., Ltd, as previously described ( 18 , 19 ). All mice were reared in an animal room at a temperature of 25°C and 50-60% humidity under a 12-h light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%